Integrating Important Vaccination Issues into the Banjar Community Religious and Socio-Cultural Values - Husairi, Ahmad; Husin, Gt. Muhammad Irhamna; Rumboko, Raihan Febri; Kurniawan, Muhammad Immas (Universitas Muhammadiyah Semarang, 2024)
Background: The important issues of vaccination need to be integrated between medical science, the Islamic religion and the religious-social-cultural values of the community. The integration is important to build public trust in the vaccination program.Objective: to integrate the important issues of vaccination into the religious and socio-cultural values of the Banjar community.Methods: The research was designed qualitatively based on a phenomenological paradigm through field observations and in-depth interviews with Banjar community participants who did not vaccinate and participants who were experts in medicine-immunology-Islamic law-social-cultural in the Banjar community. Results: The research showed that some Banjar people still did not understand the principles of vaccination, the concept of istihalah and herd immunity. The Banjar community was a religious society, that liked to work together and care about their fellow citizens.Conclusion: The principles of vaccination, istihalah, and herd immunity can be integrated with the Banjar community who are religious, like working together, and care about their fellow citizens to build public trust in the vaccination program.